Impact of the Corona Virus Disease 2019 Pandemic on Hepatology Practice and Provider Burnout. Issue 5 (28th December 2021) - Russo, Mark W.; Kwok, Ryan; Serper, Marina; Ufere, Nneka; Hameed, Bilal; Chu, Jaime; Goacher, Elizabeth; Lingerfelt, John; Terrault, Norah; Reddy, K. Rajender
Abstract : The corona virus disease 2019 (COVID‐19) pandemic has had a wide‐ranging impact on the clinical practice of medicine and emotional well‐being of providers. Our aim was to determine the impact of the COVID‐19 pandemic on practice and burnout among hepatology providers. From February to March 2021, we conducted an electronic survey of American Association for the Study of Liver Diseases (AASLD) members who were hepatologists, gastroenterologists, and advanced practice providers (APPs). The survey included 26 questions on clinical practice and emotional well‐being derived from validated instruments. A total of 230 eligible members completed the survey as follows: 107 (47%) were adult transplant hepatologists, 43 (19%) were adult general hepatologists, 14 (6%) were adult gastroenterologists, 11 (5%) were pediatric hepatologists, 45 (19%) were APPs, and 9 (4%) were other providers. We found that 69 (30%) experienced a reduction in compensation, 92 (40%) experienced a reduction in staff, and 9 (4%) closed their practice; 100 (43%) respondents reported experiencing burnout. In univariate analysis, burnout was more frequently reported in those ≤55 years old (odds ratio [OR], 2.2; 95% confidence interval [CI], 1.2‐4.2), women (OR, 2.2; 95% CI, 1.3‐3.7), nontransplant hepatology (OR, 2.0; 95% CI, 1.1‐3.3), APPs (OR, 2.7; 95% CI, 1.4‐5.1), and those less than 10 years in practice (OR, 1.9; 95% CI, 1.1‐3.3). In multivariable analysis, only age ≤55 years was associated with burnout (OR, 2.3; 95% CI, 1.1‐4.8). The most common ways the respondents suggested the AASLD could help was through virtual platforms for networking, mentoring, and coping with the changes in practice due to the COVID‐19 pandemic. Conclusion: The COVID‐19 pandemic has had a substantial impact on the clinical practice of hepatology as well as burnout and emotional well‐being. Women, APPs, and early and mid‐career clinicians more frequently reported burnout. Identified strategies to cope with burnout include virtual platforms to facilitate networking and mentoring.